The Exclusion of the Value of Justice in Court Rooms - Wilshen Leatemia; Ekberth Vallen Noya; Welly Angela Riry; Muammar Muammar (JURNAL BELO, 2022)
This article wants to criticize the practice of adjudication (judicial) which is legalistic in nature, if a judge is legalistic, then of course the basis for the judge's consideration is the law alone, regardless of what is outside the law, because in a criminal act Of course there are many factors that influence and there is also an element of cause and effect that occurs. Court judges as legal institutions that are in direct contact with a sense of justice should be able to consider outside the law. The judge is not a mouthpiece of the law, but the judge is a giver of a sense of justice. Therefore, the judge's decision is expected to be able to actualize the values ​​of Pancasila and also the judge's considerations not only based on the law alone, the State of Indonesia has a state of law, therefore as a legal state its legal products must be truly fair and able to fulfill the sense of justice sought. by the community, so that people no longer feel that this country is unfair or that the law is indiscriminate. The term legism should not be the basis for consideration of the judge's decision, but rather be a source of consideration by the judge, thereby fulfilling the sense of justice sought by the community.